The cytocompatibility of anodized surfaces for implant materials - J. Krčil; V. Březina; J. Vaněk (Czech Dental Chamber, 2019)
Introduction, aim: The oxide layers on surface of titanium alloy are influencing corrosion resistance and biocompatibility. The compatibility between the bony tissue and titanium alloy is prevalently dependent on properties of a stable titanium dioxide layer. These layers can be prepared by various methods. The oxidation process (and its conditions) is resulting in different types of oxide layer: difference in chemical composition, mechanical properties, inner structure etc. The deviation inside of the layers structure may influence the stability of the layer, its adhesion or biocompatibility.The anodic oxidation of titanium alloys in appropriate electrolyte (under certain conditions) can lead not only to creation of the oxide layer, but to creation of an oxide layer with structured surface. This kind of structure is usually characterized by pores in nanometer scale. The structured surface radically changes the interaction between the titanium alloys surface and cells; and thus influencing its behavior inside a body. The cell interaction with the structured surfaces is not properly described yet. This work aims for better understanding of such structured layers. Methods: The anodic oxidation was carried out on Ti6Al4V ELI polished samples. The oxidation process was realized in 1M H2SO4 electrolyte with the voltage 100 V and current density 50 mA/cm2. The thickness and surface morphology of the resulting oxide layer were evaluated and documented using a scanning electron microscope (SEM). The changes of color and roughness of the surface after the oxidation were observed as well.The cytocompatibility of the materials surface is expressed by a surface area colonized by cells after the three days of cultivation. This method is standardly used and accredited by ČIA. The MG63 cells were used for the experiment and the percentage of colonized surface area was evaluated. The evaluation was done on polished and oxidized Ti6Al4V ELI samples and the results were compared. Result: The structure of samples prepared using the anodic oxidation consisted of pores with size ranging from tens to hundreds of nanometers.The cytocompatibility testings showed that the cells colonized larger area on the oxidized samples. The cells covered 56.9% of the surface area of the polished samples, while 63.5% of the surface area of the anodized samples. Results of all samples exhibited Gaussian distribution. Conclusion: The anodic oxidation lead to a creation of nanostructured oxide layer on Ti6Al4V ELI samples. The cytocompatibility of this layer was compared to polished samples. It was shown that cells are colonizing the larger surface area on the oxidized samples.